BATU CAVE: PREHISTORIC OCCUPATION OF MERATUS MOUNTAINS, SOUTH KALIMANTAN: GUA BATU: HUNIAN PRASEJARAH DI PEGUNUNGAN MERATUS, KALIMANTAN SELATAN - Nia Marniati Etie Fajari; Muhammad Wishnu Wibisono (Berkala Arkeologi, 2020)
Abstract Preliminary studies in the karst hills of the Meratus Mountains in Kotabaru Regency found rock-shelters and caves that were indicated to have traces of prehistoric dwellings. One of them is Batu Cave which is in Batangkulur village, Kelumpang Barat district. This article discusses the results of excavations carried out in Batu Cave in 2018. The problems raised on proof of occupancy and how human life in the past in Batu Cave. Archaeological data were obtained from excavations by using test-pit at two different locations. The excavation findings analyses are quantitative and qualitative. Quantitative analysis was carried out to find out the quantity of findings. The qualitative analysis includes an initial classification, which divides archeological data according to the type, form and style. The results show that Batu Cave are cave dwelling with living activities that rely on the surrounding resources. Exploitation of environmental resources is seen in the use of several types of terrestrial fauna and water as one of the main food sources. Various types of tools were made using rocks, as well as bones and shells. Abstrak Studi awal di perbukitan karst Pegunungan Meratus di Kabupaten Kotabaru menemukan ceruk dan gua yang diindikasi memiliki jejak hunian prasejarah. Salah satunya adalah Gua Batu yang berada di Desa Batangkulur, Kelumpang Barat.Â Artikel ini mendiksusikan hasil ekskavasi yang dilakukan di Gua Batu pada tahun 2018. Permasalahan yang diajukan adalah apa bukti hunian dan bagaimana kehidupan manusia pada masa lalu di Gua Batu. Data diperoleh dari ekskavasi yang membuka lubang uji pada dua lokasi yang berbeda. Temuan ekskavasi dianalisis secara kuantitatif dan kualitatif. Analisis kuantitatif dilakukan untuk mengetahui kuantitas dan persentase temuan. Analisis kualitatif meliputi klasifikasi awal, yang membagi data arkeologi sesuai dengan jenis, bentuk, dan gayanya. Hasil analisis menunjukkan bahwa Gua Batu merupakan gua hunian dengan aktivitas hidup yang mengandalkan pada sumber daya di sekitarnya. Eksploitasi sumber daya lingkungan terlihat pada pemanfaatan beberapa jenis fauna darat dan air sebagai salah satu sumber makanan yang utama. Berbagai jenis peralatan dibuat dengan memanfaatkan batuan, serta sisa makanan berupa pecahan tulang dan kerang.